Resource allocation algorithm for cognitive radio systems based on STAR-RIS with coupled phase shifts - LI Guoquan; XIONG Hao; XIE Zonglin; LIN Jinzhao (Tongxin xuebao)
To address the issues of spectrum resource scarcity and limited communication quality, a scheme for a coupled phase-shift-based simultaneous transmitting and reflecting reconfigurable intelligent surface (STAR-RIS)-assisted multi-ple-input single-output (MISO) cognitive radio system was proposed. Additionally, a resource allocation algorithm aimed at minimizing the transmission power of the cognitive base station was introduced. First, under the constraints of the quality of service (QoS) for secondary users and interference limitation to primary users, a joint optimization problem was formulated to minimize the transmission power of the cognitive base station by jointly optimizing the beamforming vectors of the cognitive base station and the coefficients of the STAR-RIS. Then, it was transformed into two sub-optimization problems of active beamforming vectors and STAR RIS coefficients by the block coordinate descent (BCD) method to decoupling variables. Subsequently, based on the penalty dual decomposition (PDD) framework, the semidefinite relaxation (SDR) and the successive convex approximation (SCA) algorithms were used to optimize them alternately and seek the final solution. Simulation results show that the proposed algorithm converges well, and the proposed system scheme can achieve lower power consumption at the cognitive base station.